Identifying the level of community involvement at Kg. Kuala Telang, Kuala Lipis, Pahang - Yaman, Maheran; Baharuddin, Zainul Mukrim; Md Jani, Haza Hanurhaza (2017)
A community is a particular group of people that are bound by a similar cultural practice and activities. The continuation in the practicing the local culture developed an identity for the community. Through time, the identity is strengthened by the level of community involvement in response to their participation in preserving the culture. For that reason, in the occurrence of the lack of community involvement would be resulted in decreasing number of cultural practices. Eventually, the process contributed to causing a negative impact on the local identity. Given that, this paper addresses the importance of a community involvement in regards to safeguarding the local culture and practices. Two objectives are outlined in achieving the aim namely, to identify the list of the community activities as well as to determine the level of community involvement at Kg. Kuala Telang, Kuala Lipis. A quantitative method of analysis is adopted in the paper as to achieve the objective. The survey questionnaire is distributed to 58 respondents, and the result is analyzed using SPSS Statistics Software. The findings from the data collection are arranged into four categories, and the result is discussed accordingly as to answer the aim and objectives of the paper. As a final remark, the paper highlights the importance of community involvement and the methods to ensure the level of participation in response to community activities in the village.